The IL-33 Receptor ST2 Regulates Pulmonary Inflammation and Fibrosis to Bleomycin - Fanny, Manoussa; Nascimento, Mégane; Baron, Ludivine; Schricke, Corinne; Maillet, Isabelle; Akbal, Myriam; Riteau, Nicolas; Le Bert, Marc; Quesniaux, Valérie; Ryffel, Bernhard; Gombault, Aurélie; Même, Sandra; et al. (Frontiers in Immunology, 2018)
Idiopathic pulmonary fibrosis (IPF) is a progressive, devastating and yet untreatable fibrotic disease of unknown origin. Interleukin (IL)-33, an IL-1 family member acts as an alarmin with pro-inflammatory properties when released after stress or cell death. Here we investigated the role of IL-33 in the bleomycin (BLM)-induced inflammation and fibrosis model using mice IL-33 receptor (chain ST2) mice compared with C57BL/6 wild-type (WT) mice. Unexpectedly, 24hrs post BLM treatment ST2-deficient mice displayed augmented inflammatory cell recruitment, in particular by neutrophils, together with enhanced levels of chemokines and remodelling factors in the bronchoalveolar space and/or the lungs. At 14 days lung remodelling and fibrosis were decreased with reduced M2 macrophages in the lung associated with M2-like cytokine profile in ST2-deficient mice, while lung cellular inflammation was decreased but with fluid retention (oedema) increased. In vivo magnetic resonance imaging (MRI) analysis demonstrates a rapid development of oedema detectable at day 7, which was increased in the absence of ST2. Our results demonstrate that acute neutrophilic pulmonary inflammation leads to the development of an IL-33/ST2-dependent lung fibrosis associated with the production of M2-like polarization. In addition, non-invasive MRI revealed enhanced inflammation with lung oedema during the development of pulmonary inflammation and fibrosis in absence of ST2.